Health Seeking Behaviour pada Perawatan Kanker - Rufli, Arza; Afiyanti, Yati; Hargiana, Giur (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to synthesize the findings from existing research on health-seeking behaviors among cancer patients. A systematic review was conducted using electronic databases and websites, including Sage Journal, ProQuest, and Science Direct, on March 9, 2024. The search strategy employed a combination of MeSH terms and keywords, specifically